(untitled) (International journal of medical sciences, 2026)
This article presents a scientific analysis of the pharmacological properties of medicinal plants naturally growing in the territory of Uzbekistan. The study focuses on widely used species such as Glycyrrhiza glabra (licorice), Hypericum perforatum (St. John’s wort), Matricaria chamomilla (chamomile), Mentha piperita (peppermint), and Peganum harmala (Syrian rue). Their biologically active compounds and mechanisms of pharmacodynamic action were evaluated based on contemporary pharmacognostic and pharmacological data. The results demonstrate that these plants possess anti-inflammatory, antimicrobial, antioxidant, antispasmodic, sedative, and immunomodulatory properties. The development of phytopharmaceuticals based on local plant resources represents a promising direction for the national pharmaceutical industry.